Chronic kidney disease and coronary atherosclerosis: evidences from intravascular imaging. (3rd October 2019) - Iwai, Takamasa; Kataoka, Yu; Otsuka, Fumiyuki; Asaumi, Yasuhide; Nicholls, Stephen J; Noguchi, Teruo; Yasuda, Satoshi
ABSTRACT: Introduction : In CKD subjects, atherosclerotic cardiovascular disease (ASCVD) is a major cause of their morbidity and mortality (1–3). Current therapeutic guidelines recommend lowering LDL-C level to prevent ASCVD (4, 5). However, it remains uncertain how this therapeutic approach effectively modifies atherosclerosis of CKD. These findings suggest the need to further understand pathophysiology of atherosclerosis. Given that intravascular imaging modalities have contributed to characterize the natural history of coronary atherosclerosis (13–23), the integration of plaque imaging is expected to help to elucidate targets associated with stabilizing atheroma. Areas covered : This review will outline atherogenic stimuli in patients with CKD. In addition, the characteristics of their coronary atheroma will be presented from finding in clinical studies using a variety of intravascular imaging modalities. The efficacy of current guideline recommended anti-atherosclerotic therapies in CKD patients will be also summarized. All related articles were searched through PubMed. Expert opinion : Integration of intravascular imaging has a great potential to establish effective therapies for slowing progression of atherosclerosis in subjects with CKD. More efforts toward searching therapeutic target associated with atherosclerosis of CKD are required. In particular, identifying drivers associated with plaque calcification will lead to the development of new agents which regress calcium accumulation.